1991
DOI: 10.1007/bf01313090
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and carbon stable isotopes in the otoliths of wild and laboratory-reared Australian salmon (Arripis trutta)

Abstract: Australian salmon, Arripis trutta, collected from the east coast of Tasmania, Australia, in 1987, were weighed and measured and their otoliths marked by immersing fish in an oxytetracycline hydrochloride/seawater solution before placement in constant-temperature aquaria. Individual somatic and otolith growth rates were determined for input into mass balance models. Mass balance models were used to determine the oxygen and carbon isotopic composition of otolith material produced during captivity. There was a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
141
2
8

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(165 citation statements)
references
References 36 publications
14
141
2
8
Order By: Relevance
“…However, our estimated values of δ c -δ w are consistent with previous studies on different fish species carried out in laboratory conditions (Kalish 1991b, Thorrold et al 1997, Gao et al 2001, Høie et al 2004b). All those investigations concluded that deposition occurs at or near equilibrium in fish otoliths.…”
Section: Environmental Influences On Hake Recruits and Juvenilessupporting
confidence: 92%
“…However, our estimated values of δ c -δ w are consistent with previous studies on different fish species carried out in laboratory conditions (Kalish 1991b, Thorrold et al 1997, Gao et al 2001, Høie et al 2004b). All those investigations concluded that deposition occurs at or near equilibrium in fish otoliths.…”
Section: Environmental Influences On Hake Recruits and Juvenilessupporting
confidence: 92%
“…In otoliths, stable isotope ratios have been used to reconstruct temperature history (Devereux 1967. Mulcahy et al 1979, Kalish 1991b. Patterson et al 1993, Thorrold et al 1997b, differentiate among groups of fish (Edmonds & Fletcher 1997, Kennedy et al 1997, Dufour et al 1998, Thorrold et al 1998b, infer metabolic history , Kalish 1991c, Gauldie 1996a, Schwarcz et al 1998, and reconstruct migration history (Northcote et al 1992).…”
Section: Stable Isotopesmentioning
confidence: 99%
“…Similarly, atmospheric and oceanic d 18 O reservoirs appear to be coupled (Jouzel et al 2002), and carbonates precipitated in equilibrium with these reservoirs are affected by ambient concentrations as well as physicochemical conditions (Kim and O'Neil 1997;Thorrold et al 1997 Thorrold et al 1997;Elsdon and Gillanders 2002), and can lead to variability of otolith isotope signatures within and across years. Although otolith composition is also regulated by metabolic and physiological processes (Radtke et al 1987;Kalish 1991), these properties still yield consistent isotope signatures in otolith cores over annual time periods, justifying their use as natural tracers for specific water masses (Kerr et al 2007;Rooker et al 2008). Given the potential usefulness of otolith d 13 C and d 18 O for historical reconstructions (i.e., climate, physicochemical) and as natural tracers, evaluating the temporal variability of these signatures over decadal periods is critically needed.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature, salinity, and ambient ocean isotope concentration have all been linked to changes in otolith d 13 C and d 18 O (Kalish 1991;Thorrold et al 1997;Elsdon and Gillanders 2002), and can lead to variability of otolith isotope signatures within and across years. Although otolith composition is also regulated by metabolic and physiological processes (Radtke et al 1987;Kalish 1991), these properties still yield consistent isotope signatures in otolith cores over annual time periods, justifying their use as natural tracers for specific water masses (Kerr et al 2007;Rooker et al 2008).…”
mentioning
confidence: 99%